Integrative Assessments on Molecular Taxonomy of Acidiferrobacter thiooxydans ZJ and Its Environmental Adaptation Based on Mobile Genetic Elements - Ma, Liyuan; Yang, Weiyi; Huang, Shanshan; Liu, Rui; Li, Huiying; Huang, Xinping; Xiong, Junming; Liu, Xueduan (Frontiers in Microbiology, 2022)
Acidiferrobacter spp. are facultatively anaerobic acidophiles that belong to a distinctive Acidiferrobacteraceae family, which are similar to Ectothiorhodospiraceae phylogenetically, while are closely related to Acidithiobacillia class/subdivision physiologically. The limited genome information has kept them from being studied on molecular taxonomy and environmental adaptation in depth. Herein, Af. thiooxydans ZJ was isolated from acid mine drainage (AMD), and the complete genome sequence was reported to scan its genetic constitution for taxonomic and adaptative features exploration. The genome has a single chromosome of 3,302,271 base pairs (bp), with a GC content of 63.61%. The phylogenetic tree based on OrthoANI highlighted the unique position of Af. thiooxydans ZJ, which harbored more unique genes among the strains from Ectothiorhodospiraceae and Acidithiobacillaceae by pan-genome analysis. The diverse mobile genetic elements (MGEs), such as insertion sequence (IS), clustered regularly interspaced short palindromic repeat (CRISPR), prophage and genomic island (GI), have been identified and characterized in Af. thiooxydans ZJ. The results showed that Af. thiooxydans ZJ may effectively resist the infection of foreign viruses and gain functional gene fragments or clusters to shape its own genome advantageously. This study will offer more evidence of the genomic plasticity and improve our understanding of evolutionary adaptation mechanisms to extreme AMD environment, which could expand the potential utilization of Af. thiooxydans ZJ as an iron- and sulfur-oxidizer in industrial bioleaching.